Clinical risk factors of adverse outcomes among women with COVID-19 in the pregnancy and postpartum period: a sequential, prospective meta-analysis - Smith, ER; Oakley, E; Grandner, GW; Rukundo, G; Farooq, F; Ferguson, K; Baumann, S; Waldorf, KA; Afshar, Y; Ahlberg, M; Ahmadzia, H; Akelo, V; et al. (Elsevier, 2022)
Objective This sequential, prospective meta-analysis (sPMA) sought to identify risk factors among pregnant and postpartum women with COVID-19 for adverse outcomes related to: disease severity, maternal morbidities, neonatal mortality and morbidity, adverse birth outcomes.